Comparison of totally laparoscopic and open approach in total gastrectomy with D2 lymphadenectomy – systematic review and meta-analysis - Małczak, Piotr (Cancer Manag Res, 2018)
INTRODUCTION: Gastric cancer is a worldwide health concern, being one of the five most common malignant neoplasms worldwide. Currently, an open approach is the gold standard for surgical treatment. Incorporation of laparoscopy as a method of choice for gastric resections remains controversial because of limited evidence of eligibility. To date, there are no high-quality randomized quality trials on totally laparoscopic D2 total gastrectomies. AIM: The aim of this study was to assess currently available literature and provide meta-analysis on acquired data regarding short-term outcomes with a subgroup analysis of western and eastern studies. MATERIALS AND METHODS: We performed a systematic review and meta-analysis according to the PRISMA guidelines. The primary outcomes of interest were morbidity and short-term complications. RESULTS: An initial reference search yielded 3,073 articles. Finally, we chose eight studies covering 1,582 patients that we included in the quantitative analysis. We did not find statistical differences regarding operative time, anastomotic leakage, surgical site infection, cardiac complications, pulmonary complications, or number of harvested lymph nodes. We found significant differences regarding length of hospital stay and morbidity in the Asian population. CONCLUSION: This systematic review indicates that a laparoscopic approach for D2 total gastrectomy does not increase morbidity. Furthermore, it allows for a shorter hospital stay. However, more randomized controlled trials are required to fully assess this approach because available data are of limited quality.